2003
DOI: 10.1021/jp0303826
|View full text |Cite
|
Sign up to set email alerts
|

Stacking Faults in Formation of Silver Nanodisks

Abstract: Structural investigations by using high-resolution transmission electron microscopy (HRTEM) and selected area electron diffraction (SAED) of silver nanodisks with different sizes are presented. The disks have a face centered cubic (fcc) crystal structure and their flat surfaces are (111). Stacking faults parallel to the (111) planes are frequently observed for the nanodisks. A unique (111) stacking fault model which is parallel to the flat (111) disk surface has been proposed to explain the observed 1/3{422} f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
394
1
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(461 citation statements)
references
References 13 publications
53
394
1
13
Order By: Relevance
“…Therefore the presence of structure defects and kinetic control of growth processes are prerequisites for the preparation of Ag nanoplates [23,[29][30][31]. Due to the high surface energies at the corners of Ag TNPs [32], Ag atoms at the corners easily dissolve and may re-deposit on the edges or flat faces of the nanoplates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the presence of structure defects and kinetic control of growth processes are prerequisites for the preparation of Ag nanoplates [23,[29][30][31]. Due to the high surface energies at the corners of Ag TNPs [32], Ag atoms at the corners easily dissolve and may re-deposit on the edges or flat faces of the nanoplates.…”
Section: Introductionmentioning
confidence: 99%
“…These features are in agreement with a flattened morphology. 17,30 In addition, a minor fraction of particles exhibited rod-like shapes ( Figure 5E) characterized by the presence of (111) stacking faults ( Figure 5F). Some micrometric urchin-like ( Figure 6A) and tree-like ( Figure 6B) structures formed by aggregated and coalesced particles were also observed.…”
mentioning
confidence: 99%
“…However, the idea that different shapes of synthesized NCs could be due to template effect was found invalid as different shapes could be synthesized without changing the template shape, and even no template was involved in some cases at all [215,216]. Most recently, a method was proposed for controlling the NP shapes by considering the influence of stacking faults in certain plane as observed during the synthesis of silver nanodisks with varying size characterized by HRTEM/SAED showing the presence of forbidden 1/3{422} reflections that were proposed to be promoted by the stacking faults in [110] plane [217]. From these observations, it could be concluded that defect engineering could possibly be used in influencing the shape of NPs as confirmed in case of copper system, yielding similar results [129].…”
Section: Microemulsions Synthesismentioning
confidence: 99%